2005
DOI: 10.1002/cncr.21477
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with advanced renal cell carcinoma undergoing nonmyeloablative allogeneic stem cell transplantation

Abstract: Formation of toxic amyloid structures is believed to be associated with various late‐onset neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. The fact that many proteins in addition to those that are associated with clinical conditions have the potential to form amyloid fibrils in vitro provides opportunities for studying the fundamentals of protein aggregation and amyloid formation in model systems. Accordingly, considerable interest and effort has been directed toward developing small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 95 publications
(104 reference statements)
0
28
0
Order By: Relevance
“…However, the worldwide clinical experience of allogeneic SCT for metastatic RCC is limited, with approximately 200 cases reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]24 One of the major restrictions of this approach is the requirement that transplant candidates have an HLA-identical related donor. This requirement may limit the use of allogeneic stem cell transplantation to a minority of patients with metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the worldwide clinical experience of allogeneic SCT for metastatic RCC is limited, with approximately 200 cases reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]24 One of the major restrictions of this approach is the requirement that transplant candidates have an HLA-identical related donor. This requirement may limit the use of allogeneic stem cell transplantation to a minority of patients with metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The results of pilot reduced-intensity transplant trials for metastatic RCC are encouraging and show that responses can occur in patients with advanced metastatic disease that has failed to respond to conventional cytokine-based therapy. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15] Unrelated cord blood (UCB) is considered an alternative hematopoietic stem cell source for transplantation, and its use in adult patients with hematologic disorders is increasing. [16][17][18][19][20][21] Thus far, UCB transfer has not been attempted in patients with a solid-organ malignancy such as RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Especially busulfan, fludarabine, platinum-based chemotherapy and total body irradiation are blamed. [71][72][73][74][75][76][77][78][79][80] Various fungal factors, especially Aspergillus, and various viral factors, especially CMV and Adenovirus, may cause endothelial damage by causing an increase in soluble fms-like tyrosine kinase or thrombomodulin, PAI-1, and inflammatory cytokines. 71,81 Other potential infectious causes include parvovirus B19, HHV-6, and, most recently, BK virus.…”
Section: 71mentioning
confidence: 99%
“…A total of 43 eligible studies (7, 490 patients) were identified for this meta-analysis (25 for RCC (Atzpodien et al, 2003;Bromwich et al, 2004;Casamassima et al, 2005;Peccatori et al, 2005;Ito et al, 2006;Lamb et al, 2006;Vogl et al, 2006;Karakiewicz et al, 2007;Komai et al, 2007;Ramsey et al, 2007;Kawata et al, 2008;Ramsey et al, 2008;Tanaka et al, 2008;Iimura et al, 2009;Jagdev et al, 2010;Cho et al, 2011;Falkensammer et al, 2011;Bedke et al, 2012;Fujita et al, 2012;Sim et al, 2012;Steffens et al, 2012;de Martino et al, 2013;Yasuda et al, 2013), 10 for UC (Hilmy et al, 2005;Hilmy et al, 2006;Saito et al, 2007;Yoshida et al, 2008;Gakis et al, 2011;Saito and Kihara, 2011;Ishioka et al, 2012;Obata et al, 2012;Tanaka et al, 2012;Stein et al, 2013), and 8 for PC (McArdle et al, 2006;Beer et al, 2008;Nakashima et al, 2008;McArdle et al, 2010;Pond et al, 2012;Prins et al, ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%